1966
DOI: 10.1172/jci105349
|View full text |Cite
|
Sign up to set email alerts
|

Studies on digitalis. 13. A comparison of the effects of potassium on the inotropic and arrhythmia-producing actions of ouabain.

Abstract: Although it is generally recognized that digitalis-induced arrhythmias can be suppressed by the administration of potassium (1-3), it is not clear whether the potassium ion also influences the positive inotropic effect exerted by the glycosides on the intact mammalian heart. Clarification of this problem is important in the understanding of the interrelationships between the actions of glycosides and potassium, and is clinically significant in view of the frequency with which potassium is administered to patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1970
1970
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 34 publications
(30 reference statements)
2
10
0
Order By: Relevance
“…The single dose of each drug used was obtained from the literature as a common or usual dose. 15,[17][18][19] An additional study might be to select doses escalating from no effect to one in which signs of toxicity are manifested.…”
Section: Discussionmentioning
confidence: 99%
“…The single dose of each drug used was obtained from the literature as a common or usual dose. 15,[17][18][19] An additional study might be to select doses escalating from no effect to one in which signs of toxicity are manifested.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study would suggest that the effect of DPH and K on the positive inotropic response of ouabain should be examined under conditions in which only positive inotropy and not arrhythmia is present. Apparent increases in ouabain inotropy due to DPH and K measured near the time of ouabain toxicity (see Scherlag et al, 1968;Williams et a!., 1966) may be misleading if the enhancement in inotropy seen in the presence of the antiarrhythmic agents is thought to occur at all time periods of drug interaction.…”
Section: Discussionmentioning
confidence: 99%
“…A similar change in toxicity by variation of the extracellular potassium concentration has already been reported in the intact animal (Marcus et al, 1969 andHall et al, 1977;Steiness, 1978) On the contrary, reports on the influence of extracellular potassiumvariations on the ouabain-induced toxicity are rather divergent and support in part the (unexpected) missing effect of the altered serum-potassium concentration in the present study. Whereas some findings in the dog as well as in the rabbit indicate the well-known potassium-digitalis antagonism for ouabain (Baker, 1947;Williams et al, 1966; Lown and Wittenberg, 1968), contradictory results have been reported in the guinea pig by Greeff and Knippers (1964) and Schaumann and Chatoor (1966). Thus these differences of the potassium variation on the ouabain-induced toxicity may result from the different species used.…”
Section: Discussionmentioning
confidence: 96%